The post carbon reader: managing the 21st century's sustainability crisis (Healdsburg, 2010)
"In the 20th century, cheap and abundant energy brought previously unimaginable advances in health, wealth, and technology, and fed an explosion in population and consumption. But this growth came at an incredible cost. Climate change, peak oil, freshwater depletion, species extinction, and a host of economic and social problems now challenge us as never before. The Post Carbon Reader features articles by some of the world's most provocative thinkers on the key drivers shaping this new century, from renewable energy and urban agriculture to social justice and systems resilience. This unprecedented collection takes a hard-nosed look at the interconnected threats of our global sustainability quandary--as well as the most promising responses. The Post Carbon Reader is a valuable resource for policymakers, college classrooms, and concerned citizens."